Case study acoustic quality of fast-food, fine dining and cafe based on subjective aspects of noise - Castro, June Carla Rosales; Bautista Avigail Vergara (2008.)
The study sought to differentiate the acoustic quality of three food and beverage facilities (fast-food, fine dining and cafe) based on the observation of their physical condition and noise sources, and the assessment of the workers and diners' perceptions of the specific subjective aspects of noise namely Noise and Accident, Noise and Efficiency and Noise and Speech Intelligibility. The research design used was a descriptive case study. An ocular observation was conducted in order to document the physical condition and identify the noise sources present in the three f & b facilities. Observation sheets were accomplished and noise sources were rated. Survey questionnaires were also provided to the manager of each facility to gain basic information about the facility and its design as well as to the diners and workers to evaluate the interior design features related to acoustics and examine if the subjective aspects of noise were evident in each of the facilities. Results show that among the three facilities, the fast-food is considered the noisiest while the fine dining is the least noisy. Noise sources observed in the facilities include noise from eating utensils, equipment, furniture, conversations from people, activities by workers and diners, kitchen, cashiers area, and the outdoor. Aside from these noise sources, the physical condition of these facilities control and contribute to the production of noise mainly because acoustics is not the main priority of each of the facilities. Data obtained by the study also show that even though noise showed effects on Speech Intelligibility and Efficiency, it however did not show relationship on Accidents as perceived by the diners and workers.
Thesis (BSID)--University of the Philippines Diliman.
Keywords: Restaurants -- Philippines; Fast food restaurants -- Philippines